Videogame intervention to increase advance care planning conversations by hospitalists with older adults: study protocol for a stepped-wedge clinical trial. Issue 3 (22nd March 2021) - Mohan, D; O'Malley, A James; Chelen, Julia; MacMartin, Meredith; Murphy, Megan; Rudolph, Mark; Barnato, Amber
Abstract : Introduction: Fewer than half of all people in the USA have a documented advance care plan (ACP). Hospitalisation offers an opportunity for physicians to initiate ACP conversations. Despite expert recommendations, hospital-based physicians (hospitalists) do not routinely engage in these conversations, reserving them for the critically ill. The objective of this study is to test the effect of a novel behavioural intervention on the incidence of ACP conversations by hospitalists practicing at a stratified random sample of hospitals drawn from 220 US acute care hospitals staffed by a large, nationwide acute care physician practice with an ongoing ACP quality improvement initiative. Methods and analysis: We developed Hopewell Hospitalist, a theory-based adventure video game, to modify physicians' attitudes towards ACP conversations and to increase their motivation for engaging in them. The planned study is a pragmatic stepped-wedge crossover phase III trial, testing the efficacy of Hopewell Hospitalist for increasing ACP conversations. We will randomise 40 hospitals to the month (step) in which they receive the intervention. We aim to recruit 30 hospitalists from up to eight hospitals each step to complete the intervention, playing Hopewell Hospitalist for at least 2 hours. The primary outcome is ACP billing for patients aged 65 and older managed by participating hospitalists. We hypothesise that the intervention will increase ACP billing in the quarter after dissemination, and have 80% power to detect a 1% absolute increase and 99% power to detect a 3.5% absolute increase. Ethics and dissemination: Dartmouth's Committee for the Protection of Human Subjects has approved the study protocol, which is registered on clinicaltrials.gov. We will disseminate the results through manuscripts and the trials website. Hopewell Hospitalist will be made available on the iOS Application Store for download, free of cost, at the conclusion of the trial. Trial registration number: NCT04557930 .